Implementasi Peraturan Walikota Padang Nomor 36 Tahun 2018 Tentang Pengendalian Penggunaan Kantong Belanja Plastik di Kota Padang - Adilah Ulfah; Jumiati Jumiati (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2021)
This research describe about Implementation of Padang Mayor Regulation to controlling the use the plastic shopping bag in Padang city. Background of this research is because we find some problems of the use plastic shopping bag in Padang city. This research aims to explain about the implementation of Padang Mayor Regulation 36 of 2018 in controlling the use plastic shopping bag in Padang city. This studied use a qualitative methods and descriptive approaches. The studied was conclude at Enviromental Services in Padang. The informants are determined by thecnique purposive sampling. Data in this studieduse primary data and secondary data. Data collection was carried out by means of observation, interviews, and documentation. So the data obtained can be conclude from the data obtained in the field. The point of view of this studied is the Implementation of Padang Mayor Regulation number 36 of 2018 in controlling the use of plastic shopping bag in Padang city is not optimal. In the implementation of socialization carried out by Enviromental Services was good. But as for the constraints in implementation of this regulation of mayor is public awareness to redesign the use of plastic shopping bags is still lacking. And then, the Enviromental Services not firm in providing penalties or disincentive to business actors who still provide and eliminate plastic shopping bags at their stores. Both in modern markets and traditional markets in the city of Padang.